The mysterious sense of smell: evolution, historical perspectives, and neurological disorders - Brandt, Thomas; Huppert, Doreen (Frontiers in Human Neuroscience, 2025)
Phylogenetically, the chemical sense of smell is the oldest of all sensory modalities in terrestrial and aquatic organisms. For most non-human species in the wild, it is essential like other senses for survival because it aids nutrition, detection of environmental threats, and mating. In contrast to other senses, olfaction holds some unique properties: vertebrates, humans, and other mammals can distinguish many thousands of different odors due to genetically determined specific odorant receptors which have a lifespan of about 1 month and then are continuously replaced by neuroneogenesis in the olfactory epithelium. From a historical perspective, fragrances and perfumes played a significant role in the most influential ancient cultures, Egypt, Greece, and China. Most important was the belief in the magic power of fragrances—which were classified as “pleasant” or “unpleasant”—for medical treatment, religious or funeral rituals, e.g., preparing the bodies of the deceased for the assumed life after death, purification and divine favor. Further perfumes were used to cover natural body odor, for personal grooming, or to offer a potential hedonic odor in sexual selection. In contemporary medicine, the potential diagnostic value of olfactory loss as a biological marker for an impending neurodegenerative disorder such as Mild Cognitive Impairment, Alzheimer’s disease, Parkinson’s disease, or estimating the inflammatory activity in Multiple Sclerosis is increasingly recognized. The regeneration of odorant receptors and inhibitory interneurons provide the basis for long-term recovery of loss of olfaction due to respiratory infections, for example in pandemics like COVID-19 or after a head trauma. Imaging disorders of olfaction disclosed clinically relevant structural changes of the brain network of olfaction and the intimate reciprocal interaction with other networks to subserve higher cortical functions such as an impressive specific odor memory, quality of life, emotion, cognition, selection of food, social interaction, stress, and depression. The latter higher olfactory functions often remain undetected by both patients and their doctors. A more intensive implementation of olfactory function and clinical testing should be considered in medical training.